2009
DOI: 10.20538/1682-0363-2009-2-76-84
|View full text |Cite
|
Sign up to set email alerts
|

Problem of diagnostics of deterioration in bone strength in children

Abstract: The most part of the bone mass is formed between 10 and 14 years. The age of achievement of the peak bone mass in different parts of skeleton varies from 17 to 30 years. Low values of the peak bone mass are a significant risk factor, since the formed bone substance is expended later. Measures aimed at the early diagnostics, revealing of risk groups, and prophylaxis of reduction of the bone strength in children will favor the gain in health of children population and in the life quality in both children and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Educational regimes in School and Gymnasium were assessed to determine whether they conformed to requirements fixed in sanitary legislation. The assessment revealed that the most frequent violation involved absence of interchanges between difficult and easy subjects during a day and a week (item 10.8) 5 . The principle was violated regarding interchanges between subjects that involved different activities; subjects with different ratio of a static and dynamic component; subjects with prevailing loads on the first or second signaling system; all these violations were established in schedules of schoolchildren from all the grades in School.…”
Section: T a B L E 1 Average Chemical Concentrations Inside Classroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational regimes in School and Gymnasium were assessed to determine whether they conformed to requirements fixed in sanitary legislation. The assessment revealed that the most frequent violation involved absence of interchanges between difficult and easy subjects during a day and a week (item 10.8) 5 . The principle was violated regarding interchanges between subjects that involved different activities; subjects with different ratio of a static and dynamic component; subjects with prevailing loads on the first or second signaling system; all these violations were established in schedules of schoolchildren from all the grades in School.…”
Section: T a B L E 1 Average Chemical Concentrations Inside Classroomsmentioning
confidence: 99%
“…A comparative assessment was performed to determine whether an education regime corresponded to requirements fixed in sanitary legislation 5 ; it was done based on analyzing school schedules including lessons and breaks.…”
mentioning
confidence: 99%